A Review on Fraud Research : A Study of Vote Count - Yeni Priatnasari; Ari Kuncoro Widagdo; Evy gantyowati (Yayasan Ilomata, 2020)
This study was aimed to conduct a literature study on research related to fraud. The research method used is to use the literature study method by using the vote counting model. This research would identify papers relating to fraud that have been obtained from various existing databases. Next, the researcher classified the paper by classifying the focus of research at the paper stage in fraud prevention, detection, investigation or remediation. The results of this study were recommendations for researchers, in terms of what is still open as material in research related to fraud